The Records Of The Power Produce Of Solar Cell Of 50 Wp As Long As March 2016 At Kenten Area - Darmawi Bayin (Journal of Mechanical Science and Engineering, 2017)
Solar cell of 50 WattPeak capacity is used on this research. The measurements are conducted for eight hours a day from 9.00 o’clock a.m. till 5.00 o’clock p.m.  This research is mainly aimed at to find out the electric power outcome of the solar cell at varies weather conditions in March of 2016 year. All of the equipments and measurements apparatus is stationed at Kenten BMKG Station of Palembang. The solar cell position is facing to the north at an angle of 10º. The total output of electric power is 4384,99 Watt and the total solar light intensity 134062,91 W/m² along March 2016. On full shinny and clear day the maximum power obtained is 49,2 W/hr and the sun light intensity is 1464,6 W/m². On cloudy day, the maximum power obtained is   42,8 W/hr and the sun light intensity is 1216,9 W/m². On rainny day the maximum power obtained is 34,1 W/hr and the sun light intensity is 1042,5 W/m². The results shown the relations between the power obtained and the light intensity, atmosfir temperatur and clouds in the sky